Baseline immune profiles are associated with positive outcomes in young children with a peanut allergy, enrolled in a randomised clinical trial for oral immunotherapy - Isabelle Coenen; Abbey Figliomeni; Kimberley Parkin; Judy de Asis; Alice A. White; Sarah Miller; Jessica Metcalfe; Deborah H. Strickland; Michael O’Sullivan; Jonatan Leffler (Allergy, Asthma & Clinical Immunology, 2026)
Abstract Background Peanut allergy affects around 3% of Australian infants, can cause life-threatening anaphylactic reactions and often persists throughout life. Oral immunotherapy (OIT) is a promising treatment to achieve desensitisation, but treatment outcomes vary. This study describes the immunological profiles associated with favourable OIT outcomes. Methods This study assessed blood samples from 49 peanut-allergic children (1–4 years old) who participated in the Early Peanut Immunotherapy in Children (EPIC) randomised controlled trial. Children randomised to undergo peanut OIT ( n = 24), or to follow the current recommended clinical practise of strict peanut avoidance ( n = 25) for twelve months, were immunologically evaluated. Desensitisation outcomes were assessed using an end of treatment (EOT) oral food challenge, and blood samples were collected at baseline, 12-week follow-up (OIT only), and EOT. Thirty immune cell subsets were identified using an established immune cell flow cytometry panel and an FcεR1 expression panel. Results As part of the clinical trial, OIT induced either partial or complete desensitisation in 91.3% of participants in the intervention group, compared to 20.8% in the avoidance group. After 12 weeks of treatment, OIT-treated patients displayed an expansion of basophils, monocytes and dendritic cells compared to levels at recruitment. At EOT, OIT increased the abundance of CD4 − T effector memory cells and mast cell progenitors. Younger children with low levels of peanut-specific IgE were more likely to achieve complete desensitisation. Such outcome was also associated with low levels of CD4 + memory Tregs and CD4 − central memory T cells at recruitment, whereas increased levels of basophils were associated with partial desensitisation. Differences between partial and complete desensitisation were also observed regarding dendritic cell activation and expression of the IgE receptor. Conclusion Our findings suggest that immune signatures vary according to OIT clinical response and may have utility in monitoring treatment progress and in identifying children most likely to benefit from OIT in the future.